Medical Therapy with Pasireotide in Recurrent Cushing’s Disease: Experience of Patients Treated for At Least 1 Year at a Single Center - Yedinak, Chris G.; Hopkins, Sarah; Williams, Jessica; Ibrahim, Aly; Cetas, Justin Schultz; Fleseriu, Maria (Frontiers in Endocrinology, 2017)
Subcutaneous (SC) injection of pasireotide, a somatostatin analog, is approved for the treatment of adults with Cushing’s disease (CD) for whom pituitary surgery was unsuccessful or is not an option. We highlight the symptomatic and biochemical improvement of 6 patients with recurrent CD treated with pasireotide SC at a single center for at least 1 year. Patients were treated either through commercial use (n=5) or through the Phase 3 trial (n=1; ClinicalTrials.gov identifier, NCT00434148; study number, B2305). Most patients (n=5) were female, and the mean age at diagnosis was 35.8 years. All patients demonstrated biochemical control at 1 year of treatment. Three of the 5 real-world patients followed for more than 1 year remain on pasireotide SC, and are controlled. Two patients discontinued pasireotide SC; 1 patient because of persistently elevated urinary free cortisol levels and gallstones, and the other because of treatment for an unrelated brain tumor. Symptomatic improvement varied, but all patients demonstrated weight loss. Nausea and mild, transient injection-site reactions were the most frequently reported adverse events. Although glycated hemoglobin (HbA1c) increased after treatment initiation, 4 of 5 patients maintained HbA1c levels ≤7.0% while receiving pasireotide SC and concomitant individualized diabetes medication, if necessary. In patients who discontinued pasireotide SC, HbA1c levels decreased within 6 weeks. This report documents real-world use of pasireotide SC and indicates its effectiveness as a long-term treatment option for patients with CD. Although hyperglycemia was observed in most patients, it was managed with appropriate monitoring and treatment and was reversible upon discontinuation of pasireotide SC.